Sport Policy in Vanuatu. Issue 4 (2nd October 2017) - Kobayashi, Tsutomu; Hoye, Russell; Nicholson, Matthew
ABSTRACT: The purpose of this paper is to review the development of national sport policy in Vanuatu. The paper provides a brief synopsis of the development of national sport policy in Vanuatu and outlines the government's administrative system for implementing sport policy. It provides an analysis of government policies and objectives for sport and the nature and extent of government supported sport programmes that are focused on (1) sport for development (social development through sport); (2) junior sport development (development of sport to encourage young people to participate in regular physical activities); and (3) elite sports development. This paper highlights the dependence on foreign aid within these wide-ranging government sport policies, and questions the effectiveness of specific elements of Vanuatu sport policy, whether the processes that policymakers adopt are adequate, whether the right community of stakeholders are consulted about sport policy, and whether the development programmes from First World actually construct local ownership. While the last decade has seen considerable changes in the ways in which Vanuatu sport has been governed, developed, and funded, there remain considerable challenges for the ongoing effectiveness of sport policy interventions in this country.